3D optical displacement measurements on dynamically loaded adhesively bonded T-peel specimens. (January 2015) - Marzi, Stephan; Biel, Anders; Hesebeck, Olaf
Abstract: Adhesively bonded T-Peel specimens are loaded in a rotary impact device to investigate the behaviour of adhesive joints under high-strain rates. To gain a better understanding of that kind of tests and their results, the deformation of the samples as well as the movement of specimen support during the test is analyzed. A three-dimensional optical measurement system is used in combination with two synchronized high-speed cameras to obtain the deformations. The paper explains the experimental challenges and discusses the results of the analyses with respect to a planned usage of the experimental results in a finite element crash simulation. As main results of the investigations it can be summarized that the compliant clamping leads to an inadvertent out-of-plane-movement of the load introduction point. Based on finite element calculations it can be concluded that the measured out-of-plane-movement possesses a negligible influence on the obtained force signal, which is of primary interest in a T-Peel test.